Розробка методики створення технологічних регламентів комбінованих систем очищення стічних вод промислових об’єктів - Штепа, В. М.; Кот, Р. Є. (Енергетика і автоматика, 2017)
DEVELOPMENT OF THE METHOD OF CREATION OF TECHNOLOGICAL REGULATIONS OF COMBINED SYSTEMS OF WASTEWATER TREATMENT OF INDUSTRIAL OBJECTSV. N.  Shtepa, R. E.  KotAccording to the Ministry of Environment annually dumped untreated into surface waters 3 billion. Cube. meters of water.Industrial waste water is approximately 8-10% of the total volume of wastewater, but the degree of contamination of the percentage is much higher. It is necessary to note that in recent years the volume of industrial waste water decreased by about 30%. Industrial waste water after appropriate cleaning can be reused in the process, which in many industrial water recycling systems are created or closed (stagnant) water supply and sewage systems, in which precluded any discharge into water bodies.Accordingly, there is a pressing task of developing technical regulations operation of the combined electrotechnological treatment of industrial wastewater.The aim - to study and develop methods of creating technical specifications combined water purification systems in view of emergency situations.Setting performance criteria for equipment efficiency has allowed to fulfill requirements for quality water treatment while minimizing resource intensive- energy efficiency criteria for the month (March 2017) had zero deviation ± 3,4%.During the operation the combined electrotechnological purification installations have been no going beyond technology (environmental) requirements for water quality. An actual financial costs (22 working days, 402 m3 / month) was about 100 dollars (0.24 dollars / 1 m3).For comparison, the cost of wastewater treatment reagent - 0.5 dollars per 1 m3. In view of the minimal available space in other ways as unique not considered.Production of energy efficient methods of study and implementation combined electro-technological plants remove pollutants from water solutions allow the company to perform environmental quality requirements spillway, while implementing the scheme water resouce supply - Purified water is re-used in the process.The results allowed the production equipment used to formulate the concept on methods for creating relevant technical regulations.The technique of creating technical regulations based on industrial research and notation Unified Modeling Language UML, which is independent of the technology and used to model systems, including multiparameter, using object-oriented paradigms.Precedent consider only one - "Development of technical regulations" based on the fact that the intermediate precedents (methods for measuring metrological data, predictive modeling processes combined electrotechnological water purification equipment design of sewage treatment, etc.) justified, developed, technologically determined by simulation and have been manufacturing implementation .Stages of development of technical regulations electrotechnological combined sewage different-industrial facilities iterative and repeated in documents created to develop: flowsheet and functional modes of offsetting potential emergency situations of natural and man-made disasters; range and combined modes of water purification equipment based on comprehensive consideration of financial investment and energy efficiency criteria.In the case of the developed method is recommended to provide continuous cooperation and periodic monitoring of the situation of energy efficiency and investment and financial performance of the equipment.You must create two versions precedent "Development of technical regulations" because there are two states: designing new treatment facilities company (stage "Project") operating and upgrading treatment plants. The differences will lie only a few events mainstream media.ConclusionsEstablished methods develop technical specifications of sewage through the use of hardware design combined electrotechnologies purification and intellectual information and functional design will eliminate the classic disadvantages of creating such documents and take into account the effect of abnormal situations of anthropogenic and natural origin, a complex set requirements for energy efficiency and investment and financial components operation of water treatment plants.